Barriers to Green Financing in Developing Nation: An Investor’s Perspective for Promoting Sustainable Development - Chaudhary, Manoj Kumar; Adhikari, Madhav; Shakya, Nimisha (International Research Journal of MMC, 2024)
Green financing plays a pivotal role in addressing environmental challenges and fostering sustainable development, particularly in emerging economies. However, its adoption is often hindered by systemic barriers. This study examines the barriers to green financing in Nepal, focusing on four critical factors: the incapability of banks and financial institutions (BFIs), limited accessibility, political constraints, and public perception. Using a quantitative, cross-sectional survey design, data were collected from 228 investors across Nepal’s Kathmandu Valley. Statistical analyses, including correlation and regression, reveal that all four factors significantly influence investor participation in green financing, with political constraints and accessibility emerging as the most prominent barriers. The findings highlight a considerable communication gap, insufficient institutional capacity, and weak policy support as key obstacles. This study underscores the need for enhanced public awareness, institutional capacity building, and supportive regulatory frameworks to overcome these challenges. By addressing these barriers, Nepal can unlock the potential of green financing, advancing its sustainability goals and economic resilience. The research contributes valuable insights to the growing body of literature on green finance, offering actionable implications for policymakers, financial institutions, and investors in similar emerging markets.